Unobserved Heterogeneity; Process and Parameter Effects in Life Insurance - Jaap Spreeuw; Henk Wolthuis (Tinbergen Institute, 1997)
In this paper life insurance contracts based on an urn-of-urns model, with age-at-death asobservable variable, are analyzed. Premium payment functions based on the principles of“equivalence on an individual level” and “equivalence on a group level” are compared. Boththe aggregate loss and its second moment for an individual contract are split in severalcomponents. Life insurance contracts are compared with non-life insurance contracts, alsowith respect to solidarity.
Keywords: 330; Lebensversicherung; Versicherungsmathematik; Theorie